2017
DOI: 10.1002/lary.26872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supramaximal balloon dilatation pressures on adult cricoid and tracheal cartilage: A cadaveric study

Abstract: NA. Laryngoscope, 128:1304-1309, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…1 Balloon dilation does carry some risk including tracheal laceration, cricoid fracture, and dilation of healthy trachea leading to potential disruption of normal tracheal mucosal tissue. 2 First described in the literature in 2013, CO2 laser wedge excisions are an alternative to traditional balloon dilation. This method involves excision of large wedges of stenotic tissue with preservation of small bridges to allow for re-mucosalization and prevention of circumferential scarring.…”
Section: Introductionmentioning
confidence: 99%
“…1 Balloon dilation does carry some risk including tracheal laceration, cricoid fracture, and dilation of healthy trachea leading to potential disruption of normal tracheal mucosal tissue. 2 First described in the literature in 2013, CO2 laser wedge excisions are an alternative to traditional balloon dilation. This method involves excision of large wedges of stenotic tissue with preservation of small bridges to allow for re-mucosalization and prevention of circumferential scarring.…”
Section: Introductionmentioning
confidence: 99%
“…However, tracheal rupture usually does not occur even when high pressure is applied to the tracheal wall, due to the resiliency of the trachea. [ 6 ] Therefore, the factors causing intubation injury also need to be considered. Several studies have found that multiple factors may lead to tracheal rupture following intubation, such as repetitive forceful attempts, overinflation of the balloon cuff, incorrect tube size, and improper tube positioning.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to limit the dilating time, as breathing is stopped during balloon dilatation. Furthermore, the trachea should be carefully observed after cicatricial repair, which may restrict all the tractional forces; it may exhibit a different behavior owing to reduction in its elasticity and strength [11]. Now it is possible to use a tracheal/bronchial balloon whose diameter changes with 3 stages of expansion pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Now it is possible to use a tracheal/bronchial balloon whose diameter changes with 3 stages of expansion pressure. A large mismatch between the balloon catheter diameter and the inner diameter of the airway stenosis may cause edema of the airway walls, bronchial spasm, deep ulceration [10], cartilage fracture, and airway rupture [11]; therefore, it is useful to gradually expand the inner diameter, as predicted by chest CT. In our case, the balloon diameter for dilatation was selected so as to not exceed the tracheal diameter predicted by chest CT, and the pressure required to obtain the expanded diameter was taken as the expansion pressure.…”
Section: Discussionmentioning
confidence: 99%